Routledge handbook of critical terrorism studies - Jackson, Richard 1967- HerausgeberIn; George Routledge & Sons (Routledge handbooks, 2016)
Introduction: a decade of critical terrorism studies / Richard Jackson -- Critical approaches to the study of "terrorism" -- The emergence of terrorism studies as a field / Lisa Stampnitzky -- Critical terrorism studies after 9/11 / Lee Jarvis -- The real and the bluff : on the ontology of terrorism / Joseba Zulaika -- Critical epistemologies of terrorism / James Fitzgerald -- Post-structuralism and constructivism / Charlotte Heath-Kelly -- Critical theory and terrorism studies : ethics and emancipation / Harmonie Toros -- The historical materialist approach to critical terrorism studies / Douglas Porpora -- Methodology and the critical study of terrorism / Jacob Stump -- The nature and causes of "terrorism" -- The definition of "terrorism" / Timothy Shanahan -- The narrative of terrorism as an existential threat / Jessica Wolfendale -- New versus old terrorism / Alexander Spencer -- Religion and terrorism / Ioannis Tellidis -- Female terrorism and militancy / Caron Gentry and Laura E. Sjoberg -- State terrorism -- Understanding western state terrorism / Ruth Blakeley and Sam Raphael -- Torture / Robert Brecher -- Rendition in the "war on terror" / Sam Raphael and Ruth Blakeley -- Targeted killing and drone warfare / Laurie Calhoun -- Contemporary responses to terrorism -- The language of counterterrorism / Jack Holland -- Critical evaluation of counterterrorism / Sondre Lindahl -- A critical perspective on the global war on terror / Paul Rogers -- The governmentality of terrorism: uncertainty, risk management, and surveillance / Luca Mavelli -- Radicalization, de-radicalization, and counter-radicalization / Lasse Lindekilde -- Emerging debates -- Eco-terrorism and expansionary counter-terrorism / John Sorenson -- Media coverage of terrorism / Ben O-Loughlin -- Collective memory and terrorism / Charlotte Heath-Kelly -- Terrorism and peace studies / Ioannis Tellidis